1999
DOI: 10.1007/s001270050189
|View full text |Cite
|
Sign up to set email alerts
|

Parent-adolescent agreement on emotional and behavioral problems

Abstract: Many adolescents in need of psychiatric assessment do not receive appropriate help because their problems remain unnoticed by adults. Internalizing problems among girls seem especially likely to remain unrecognized by adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
190
15
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(234 citation statements)
references
References 0 publications
23
190
15
6
Order By: Relevance
“…Those findings contrast other studies, which showed that adolescents reported more internalizing Table 5 Post-hoc differences between CBCL and YSR using paired t tests Gender and externalizing problem behavior than their parents [34,35]. Sample characteristics might be able to explain the differences between our study and previous ones.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Those findings contrast other studies, which showed that adolescents reported more internalizing Table 5 Post-hoc differences between CBCL and YSR using paired t tests Gender and externalizing problem behavior than their parents [34,35]. Sample characteristics might be able to explain the differences between our study and previous ones.…”
Section: Discussioncontrasting
confidence: 99%
“…Sample characteristics might be able to explain the differences between our study and previous ones. Most of the earlier studies assessed parentyouth agreement among the general population [12,24,35]. For example, Phares and Danforth [31] assessed adolescent and adult reports of distress over clinically referred adolescents' problems and found that parents were more bothered by both, internalizing and externalizing behaviors than adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the use of multiple informants (e.g., mother and self-report) on measures of peer victimization and internalizing symptoms is infrequent. Agreement between different informants on emotional and behavioral problems or victimization is typically low Sourander et al 1999). However, if victimization reports from different informants show a consistent relationship to later internalizing problems this substantially adds to the validity of a causal relationship between both (Rønning et al 2009).…”
mentioning
confidence: 99%